Spectroscopic Studies on the [4Fe-4S] Cluster in Adenosine 5′-Phosphosulfate Reductase from Mycobacterium tuberculosis - Bhave, Devayani P. (American Society for Biochemistry and Molecular Biology, 2011)
Mycobacterium tuberculosis adenosine 5′-phosphosulfate reductase (MtAPR) is an iron-sulfur protein and a validated target to develop new antitubercular agents, particularly for the treatment of latent infection. The enzyme harbors a [4Fe-4S](2+) cluster that is coordinated by four cysteinyl ligands, two of which are adjacent in the amino acid sequence. The iron-sulfur cluster is essential for catalysis; however, the precise role of the [4Fe-4S] cluster in APR remains unknown. Progress in this area has been hampered by the failure to generate a paramagnetic state of the [4Fe-4S] cluster that can be studied by electron paramagnetic resonance spectroscopy. Herein, we overcome this limitation and report the EPR spectra of MtAPR in the [4Fe-4S](+) state. The EPR signal is rhombic and consists of two overlapping S = ½ species. Substrate binding to MtAPR led to a marked increase in the intensity and resolution of the EPR signal and to minor shifts in principle g values that were not observed among a panel of substrate analogs, including adenosine 5′-diphosphate. Using site-directed mutagenesis, in conjunction with kinetic and EPR studies, we have also identified an essential role for the active site residue Lys-144, whose side chain interacts with both the iron-sulfur cluster and the sulfate group of adenosine 5′-phosphosulfate. The implications of these findings are discussed with respect to the role of the iron-sulfur cluster in the catalytic mechanism of APR.